2μm widely tunable thulium-doped fiber laser seed oscillator. Issue 2 (March 2021) - Hu, Peixin; Ji, Encai; Nie, Zilin; Deng, Jinchao; Yao, Lu; He, Zhengdi
Abstract: 2μm band laser can be used in transparent plastic welding, soft tissue laser surgery, LiDAR, toxic hazard gas sensing and medium-and far-infrared parametric oscillation conversion. However, there are still many problems that need to be clarified on how to break through the peak power limit, realize pulse time domain programmable and laser wavelength wide range tuning in the nanosecond thulium fiber system. In this experiment, wide tuning laser at 2μm band was used to realize different laser wavelength, constant seed laser power output, and EOM was used to define laser pulse waveform and pulse frequency.